Les voies de la (re)connaissance. - Eve Gianoncelli (Genre, Sexualité et Société)
This article aims to examine the ways in which different conceptions (national, disciplinary, ideological) can play a part in the process of reception, through the case of the woman artist and intellectual Claude Cahun. It intends to show the ways in which the processes of rediscovery have been shaped in antagonistic ways between “French” and “American” genealogies which consist in different relations to the surrealist issues and to those dealing with gender and / or sexuality. They are part of the larger opposition between universalism and communitarianism, French intellectual world and US artistic world and of opposite conceptions of the subject, abstract from one hand, situated to the other hand. In differing ways, these oppositions converge to insist upon the exceptional and subversive status of Cahun. In conclusion, I propose to highlight my own standpoint and the ways in which the category of “woman intellectual” may help to better understand Cahun’s forms of experience and subjectivity.